Method for determining crystal defect concentration below 10 ppm in semiconductor material based on light modulation reflection measurement

By combining light modulated reflection measurement and reference measurement, considering the impact of low defect concentration in semiconductors, the challenge of measuring defect concentration in ppm-ppb order in semiconductors is solved, and accurate analysis of charge carrier lifetime and defect site concentration is achieved. , improves the quality control of semiconductor materials.

CN119487385APending Publication Date: 2025-02-18SEMILAB ZRT
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380028053.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-03-18
Filing Date
2023-03-14
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In semiconductors, prior art is difficult to accurately measure and analyze low defect concentrations on the order of ppm-ppb, especially when deriving charge carrier lifetimes and defect site concentrations in light modulated reflection measurements.

Method used

By combining light modulated reflection measurements and appropriate reference measurements, taking into account the influence of structural defect sites or pollutant atoms, a high-precision non-destructive method is used to derive the charge carrier lifetime and defect site concentration in semiconductors.

Benefits of technology

Accurate measurement and analysis of low defect concentrations are achieved, important information on the impact of defect sites on charge carrier lifetime, and improved the quality control and electrical properties of semiconductor materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119487385A_ABST
    Figure CN119487385A_ABST
Patent Text Reader

Abstract

For a semiconductor sample, the method is capable of determining charge carrier lifetime and crystal defect concentration associated with composite defect centers present in the material based on light modulated reflection (PMR) measurements operating within a quasi-static modulation frequency range. Defect centers present in a substantially single crystal semiconductor sample (M1) may be endogenous or extrinsic origin, typically electro-active defect (de-feed) sites created by the implantation of low mass-H +, He + high energy ions or impurity atoms (e.g., metal contaminants introduced in other technical steps). The method can be used in all cases where the crystal defect concentration is typically in the ppb-ppm range, the depth distribution is almost uniform, and the size of the excitation / analysis laser spot in the PMR measurement is significantly smaller than the thickness of the region containing the crystal defect. The total lifetime tautot is given from the excessive charge carrier concentration obtained from PMR measurement by using the program, and the lifetime and concentration allocated to endogenous or exogenous defects can be determined according to the total lifetime by knowing the lifetime of other charge carrier recombination and the time constant of the diffusion process. And the lifetime and concentration may be associated with injection or other technical parameters.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for deriving charge carrier lifetime and defect site concentration from light modulated reflectance measurements in the presence of low defect concentrations of the order of ppm-ppb in semiconductors, and more precisely to a method for determining crystal defect concentrations below 10 ppm in semiconductor materials based on light modulated reflectance measurements. Background Art

[0002] Photomodulated reflectivity (PMR for short) is a non-destructive, non-contact test technique widely used in semiconductor technology, whereby samples can be optically inspected after one technological step at a time (e.g., immediately after ion implantation and before a subsequent thermal treatment step).

[0003] From previous studies, for example, from F. A. Pongrácz, Kun, J.Szívós, B.Bartal, B.Fodor,A. - Molnár, Gy. Nádudvari, J. Byrnes, and LM Rubin, “Mid-lowenergy implantation tilt angle monitoring with photomodulated reflectance measurement, Proceedings of the 30th Annual SEMI Advanced Semiconductor Manufacturing Conference (ASMC), Saratoga Springs, NY, USA, May 6-9, 2019, pp. 1-4”, and from A. Pongrácz, J. Szívós, F. Zs Zolnai, Sepsi, A. Kun, Gy. Nádudvari, J. Byrnes, L. M. Rubin, E. D. Moore, “Tilt angle and dose rate monitoring of low energy ion implantation processes with photomodulated reflection measurement, Proceedings of the 31st Annual SEMI Advanced Semiconductor Manufacturing Conference (ASMC), Saratoga Springs, NY, USA, August 24-26, 2020, pp. 1-4”, the measured PMR signal shows a high sensitivity to the ion implantation dose, and from Z. Zolnai, F. Korsós, A. Pongrácz, V. Samu, Z. Kiss, B. Fodor, J. Szivós, L. Rubin, E. Moore, and J. Byrnes, “Room temperature micro-photoluminescence measurements for monitoring defects in low-energy high-dose As and Bimplanted According to the paper Room-temperature microphotoresist measurements for monitoring defects in low-energy, high-dose As- and B-implanted silicon (Proceedings of the 32nd Annual SEMI Advanced Semiconductor Manufacturing Conference (ASMC), Saratoga Springs, NY, USA, May 10-12, 2021, pp. 1-4), the measured PMR signal shows high sensitivity to the current density of the ion implantation, the energy and mass of the implanted ions, and, in the case of channel implantation, to the tilt of the ion beam with respect to the channel crystal axis.

[0004] In addition, due to the small sampling area of ​​a few square millimeters, PMR is also suitable for high-resolution sample mapping and sample homogeneity testing after the application of the technical steps. Therefore, the technical and theoretical development of this method may be of great significance to semiconductor technology and materials science.

[0005] The PMR technique primarily measures the change in reflectance of a sample under light excitation, but this parameter is also related to many other physical properties of the measured material and provides information about these properties. For example, in the case of shallow and ultra-shallow p-n, the exact depth of the transition can be determined, usually in the range below 100 nm, as known from the study by F. Dortu, T. Clarysse, R. Loo and W. Vandervorst "Extracting active dopant profile information from carrier illumination power curves, J. Vac. Sci. Technol., B 24, p. 375, 2006". The theoretical background of the PMR effect, i.e. methods for calculating the PMR signal in p-type and n-type semiconductors doped with different concentrations, is discussed in detail in the literature, for example in the study by F. Dortu, T. Clarysse, R. Loo, B. Pawlak, R. Delhougne and W. Vandervorst, “Progress in the physical modeling of carrier illumination, J. Vac. Sci. Technol., B 24, p. 1131, 2006”, or in the study by F. Dortu, “Low frequency modulated optical reflectance for the one-dimensional characterization of ultra-shallow junctions, PhD thesis, IMEC, Leuven, Belgium, 2009”. In these studies, the values ​​of the material parameters associated with the PMR effect in single-crystalline Si samples are also reported.Methods for deriving the total charge carrier lifetime from the PMR signal are also described, which are not only applicable to Si but also, for example, in the context of studying the free charge carrier dynamics of InGaN / GaN quantum valley structures, see, for example, the study by A. Salnick, A. Mandelis, A. Othonos and C. Christofides in “Noncontact lifetime reconstruction in countinuously inhomogeneous semiconductors: generalized theory and experimental phototermal result for ion-implanted Si”, Review of Progress in Quantitative Nondestructive Evaluation, Vol. 16, ed. Thompson and D. E. Chimenti, Plenum Press, New York, 1997, pp. 371-378; or the study by X. Lei, B. Li, Q. Sun, J. Wang and C. Gao in “Electronic transport characterization of B+ ion-implanted silicon wafers with nonlinear or MP Halsall, I.F. Crowe, J. Mullins, R.A. Oliver, M.J. Kappers, and C.J. Humphreys, “Photomodulated Reflectivity Measurement of Free-Carrier Dynamics in InGaN / GaN Quantum Wells,” ACS Photonics 5: 4437-4446, 2018.

[0006] However, in the tested ion-implanted Si samples, when the PMR effect in the damaged layer is dominated by the thermo-optical effect rather than the electro-optical effect, the defect density falls into the high range, typically 0.1-1% or more, and the defect concentration is highly non-uniform with depth. On the other hand, ion-implanted and subsequently heat-treated Si samples were examined, where the defect structure and defect concentration distribution present are less well known, e.g., in addition to residual complex defects, end-of-range (EOR) errors may be present in the sample. In another study, in the case of InGaN / GaN, the samples have a single-crystalline structure at a given doping level and may not contain structural defect sites, which may, for example, be caused by ion implantation or unwanted contaminants (e.g., metal impurities that entered the sample during the production of the raw materials used or post-processing steps). Here, the presence of these error locations is not taken into account when evaluating the PMR signal.

[0007] However, from a semiconductor technology point of view, it is important in many cases to know the amount of structural defects in small concentrations of ppm or even ppb, as well as the defect sites that can be associated with impurity atoms and their influence on the electrical properties (carrier lifetime).

[0008] In this specification, a method is proposed which is a step forward compared to previous work, which, in combination with the use of suitable reference measurements, also takes into account the influence of structural defect sites or contaminant atoms present in a basic single-crystalline sample in small concentrations and in an almost uniform distribution when evaluating the PMR signal. In these cases, the PMR effect is dominated by the electro-optical effect and a significant excess charge carrier concentration can remain in the sample. By this method, information can be obtained about the influence of typical deep energy levels caused by defect sites in the band gap on the charge carrier lifetime and their concentration. Using this method, the lifetime of point defects in the lattice can be derived from the lifetime value of the entire charge carrier after separating other lifetime contributions to the overall effective lifetime, such as the contributions of the characteristic time constants of Schokley-Read-Hall recombination, Auger recombination and charge carrier diffusion.

[0009] Both the defect concentration and the specific lifetime values ​​obtained in this way are important parameters from a technological and materials science point of view.

[0010] The first publications concerning the measurement method outlined are older, but from the late 80s, and can be found in US 4,579,463 or JP H0289335. In general, light modulated reflection can be denoted by this and other names: thermal wave, modulated optical reflection (MOR), etc. US 6,489,801 B1 lists all the physical properties that may influence the measured reflection signal, but does not discuss them qualitatively.

[0011] Some well-known documents discuss manufacturing technology solutions used in ion implantation processes, mainly their monitoring. WO 99 / 08307A1 describes the calibration of an ion implanter to a previously measured dose. US 6,812,717 B2 discloses the correspondence of measured values ​​to "parameters used to create the measurement" (e.g., ion implantation control parameters), or conclusions about the lateral diffusion drawn by comparing a specially designed geometry with the distribution of measured values, and based on this, discloses the application of the decision condition "accept-reject" in the manufacturing process.

[0012] JP H01134240A proposes a solution for determining the variation of the depth distribution of mesh defects on grindings of different depths without quantitative measurement.

[0013] US 8,120,776 B1 describes the use of the DC component of light modulated reflectometry to determine the properties of ultra-shallow pn, wherein the lattice defect concentration is determined based on a comparison with a DC signal obtained on a preliminary reference sample.

[0014] The correlation between the TW signal and the implanted dose has long been studied using the aforementioned “thermal wave” (TW) technique. For example, S. Hahn et al. also reported that the TW signal was correlated with the implanted dose at a relatively high dose of 100 keV Ar+ (10 13 -10 15 cm -2 ) and 100keV Si+ (dose 10 14 -10 15 cm -2 Defect concentration and TW signal measured by deep level transient spectroscopy (DLTS) in the heat treated sample after near-amorphous / amorphizing implantation of ). The defect density in the heat treated sample is in the ppb range. A qualitative correlation was established, but no error density was derived from the TW signal.

[0015] M.Anjum et al. used TW technique to study the 0.5-3MeV (dose 10 12 -10 14 cm -2 ) High Energy P + The influence of implantation (see Nucl. Instrum. Methods Phys. Res. B 55 (1991), 266-268). For a channel-directed implantation with 2 MeV energy, correlations between dose and TW signal, and between tilt angle and TW signal were found, but the estimation of defect concentration was not resolved.

[0016] W.Kiepert et al. studied the use of laser modulated optical reflection of 100keV He + (The dosage is 10 11 -10 15 cm -2 ) implanted Si samples (Surface and Coatings Technology, 116–119 (1999) 410–418). Here, the low energy implantation affected only the upper 1 μm of the sample and produced defect concentrations in the range of 0.1–1% ppm, which is high from the perspective of this method. The authors did not discuss the effect of defect concentration on carrier lifetime when modeling the measured signal.

[0017] A. Salnick et al. in their study "Review of Progress in Quantitative Nondestructive Evaluation (Volume 16, edited by DO Thompson and DE Chimenti, Plenum Press, New York, 1997, pp. 371-378)" studied the 50 keV P by photothermal reflectance (PTR) before and after heat treatment. + (The dosage is 10 13 cm -2 ) implanted Si samples. Their goal was to perform a depth-dependent assessment of the carrier lifetime and diffusion coefficient. By means of computer simulations, the intensity and phase of the measured PTR signal were adjusted depending on the modulation frequency. In the implanted samples examined, the defect density can be said to be high, typically 0.1-1%, and the defect concentration is highly non-uniform with depth. On the other hand, the defect structure and defect concentration distribution formed in the heat-treated samples are less well known, which means that in addition to residual complex bulk defects, end-of-range (EOR) defects may also be present. The authors later repeated the wide (10 9 -10 15 cm -2 )Dose range 100keV B + , P + 、As + For an analysis of the implantation, see A. Salnick and J. Opsal, Journal of Applied Physics 91, 2874, 2002. The shallow defect structure is qualitatively different from the samples we examined. The authors did not evaluate the lifetime of the defect state.

[0018] X. Lei et al. used photogenerated charge carrier radiometry (PCR) to measure the 100 keV B + Ion implantation (dose 1011 -10 16 cm -2 ) and heat-treated Si samples and evaluated depending on the modulation frequency, with a similar purpose to the previously mentioned Salnick study (Journal of Applied Physics 127, 035701 (2020)). Information on the entire charge carrier lifetime was obtained, but the defect recombination-related lifetime was not evaluated. In similar tests, highly inhomogeneous sample structures, such as shallow defect distribution, diffusion during heat treatment, the presence of end-of-range (EOR) defects after heat treatment, etc., lead to more complex and uncertain evaluations than the method according to the invention (for examining almost uniformly distributed non-heat-treated defect structures extending to great depths).

[0019] MP Halsall et al. studied single-crystalline, non-implanted InGaN / GaN structures using PMR technology and evaluated the charge carrier lifetime based on lasing, taking into account SRH, Auger and radiative recombination processes (see ACS Photonics 5: 4437-4446 (2018)). The presence of structural defects was not considered. Summary of the invention

[0020] The object of the present invention is to be able to determine the defect recombination-related lifetime of missed charge carriers in the above-mentioned examples.

[0021] The present invention is based on the recognition that the crystal defect concentration, which has been widely neglected so far, plays an important role in the charge carrier lifetime and that, when determining the latter, low crystal defect concentrations in the ppm-ppb range should also be taken into account, which can be advantageously performed using light modulated reflectance measurements with reliable results.

[0022] The set task has been solved by a method according to the features of claim 1 for deriving charge carrier lifetime and defect site concentration in semiconductors from light modulated reflectometry at low defect concentrations in the ppm-ppb range. Advantageous implementations of the method are listed in the dependent claims.

[0023] Monitoring of implant dose and charge carrier lifetime using high precision, non-destructive methods is an important factor in the manufacturing process. The method based on PMR analysis according to the present invention can be well used for this. In the case of C-MOS based imaging electronics, it is also important to monitor the presence of metallic impurities (Fe, Cr, etc.) that affect the stable operation of the device and their impact on the charge carrier lifetime in the starting semiconductor substrate wafer. The PMR based method can also be used here for certain contaminant concentration ranges. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The present invention will be described in more detail by means of implementation examples with reference to the accompanying drawings, in which

[0025] Figure 1 A flow chart showing a possible implementation of the proposed method for ion implantation into a sample,

[0026] Figure 2 The results show that the lightly doped (~10 -15 cm -3 ) Example of DR / R0 values ​​calculated for Si samples,

[0027] Figure 3a and 3b shows the concentration versus depth of vacancy defect centers created by 1.5 MeV hydrogen ion implantation in a single crystal Si sample,

[0028] Figure 4 shows the PMR signal measured for the Si sample implanted under the conditions shown in FIG3 and the reference measurement value,

[0029] Figure 5 The charge carrier lifetime contribution and the effective diffusion time constant obtained from PMR measurements using the proposed method are shown as a function of the implantation dose. DETAILED DESCRIPTION

[0030] PMR Technology Introduction

[0031] The working principle of PMR technology is based on the fact that the complex refractive index of a sample changes due to optical excitation. This change manifests itself as a change in reflectivity, which can also be detected optically.

[0032] In the case of PMR, a single-mode laser is used to excite and measure the resulting changes in reflection. In the case shown, the excitation laser has a wavelength of 808nm, while the measurement laser has a wavelength of 980nm. These lasers are connected to an optical fiber and then focused on the sample to form a common spot with a diameter of about 3μm, so the technique can achieve excellent spatial resolution. Due to the use of near-infrared wavelengths, the measurement is not only non-contact but also non-destructive.

[0033] To detect the PMR-induced reflectance change (ΔR), the intensity of the excitation laser incident on the sample is modulated strictly sinusoidally, in our case at 2kHz, while the intensity of the incident measurement laser is kept constant. When measuring the reflected intensity of the laser, we use the measurement technique to "lock" to the Fourier amplitude corresponding to the modulation frequency of 2kHz. The "raw" PMR signal RawPMR is defined as the quotient of the Fourier amplitude obtained from the reflected signal of the measurement laser (that is, the alternating current, i.e., the AC component) and the direct current (i.e., the DC component of this reflected signal). This ratio actually gives the relative reflectivity change: RawPMR = I refl AC / I refl DC =ΔR / R.

[0034] In the case of semiconductor materials, the causes of reflectivity changes are the generation of excess charge carriers (electrons and holes) and the formation of temperature gradients during optical excitation.

[0035] When examining ion-implanted semiconductor samples, the PMR signal is also affected by changes in the charge carrier concentration caused by lattice damage resulting from the ion implantation. The PMR technique is therefore sensitive to all parameters of the implantation process (e.g., ion mass, ion dose, ion energy, ion beam current density, ion beam direction, and in the case of channel implantation, i.e., tilt and twist angles relative to the main crystal axes / planes) and even to the magnitude of the implanted ion current density. Since the PMR signal generally exhibits a nonlinear dependence, the sensitivity varies depending on the parameters and also on their different ranges.

[0036] In the method according to the invention, the dose dependence of the PMR signal is followed for 1.5 MeV high energy hydrogen ion implantation. The state-of-the-art knowledge required to implement the method which is not described in detail in this specification is known to the person skilled in the art.

[0037] Figure 1 A flow chart showing a possible implementation of the proposed method in the case of ion implantation of a sample M1 is shown.

[0038] Conditions, approximations and parameters required to implement the method

[0039] The charge carrier lifetime and concentration, which can be assigned to the defect site, and the contaminant atom concentration can be derived from the PMR signal measured in step S1, provided that the semiconductor sample M1 satisfies the following conditions:

[0040] (i) Sample M1 is considered to have a substantially single-crystalline structure containing low ppm-ppb concentrations of electrically active defect sites. Defect sites can be defect centers created during ion implantation with energies of about 1-10 MeV, e.g., in the case of Si, they are typically vacancies, divacancies, dangling bonds, or impurity atoms located at substitutional or interstitial lattice sites, such as defect centers associated with metallic impurities such as Fe, Cr, Ni, etc. The defect concentration N def The maximum penetration depth R from the sample surface to the implanted ions is considered to be p is uniform and within the contamination depth range. The capture (recombination) cross section of a free charge carrier defect site is s def .

[0041] (ii) Due to the low defect concentration, usually 10 13 -10 16 cm -3 , it is therefore assumed that the lattice essentially retains the physical properties characteristic of an undamaged single crystal, and that excess defect sites cause only local perturbations that essentially affect only the charge carrier lifetime. Therefore, in the following, where material parameters influence the PMR effect, values ​​valid for single-crystalline materials will be used, assuming that these have sufficient accuracy.

[0042] (iii) The lateral bipolar diffusion and thermal diffusion model defined in the process, i.e., the characteristic diffusion time, can be used to excite and sample the radius R of the laser spot las In the case of geometries that are significantly smaller than the thickness of the region containing the defect, in the case of ion implantation, the maximum ion penetration depth R p (i.e. R las < <R p ) situation.

[0043] (iv) Due to the modulation frequency f of the excitation laser mod Lower (in the above case f mod = 2kHz), therefore, it is assumed that the changes caused by consecutive modulation cycles in sample M1 have no temporal overlap between adjacent modulation cycles. The modulation effect is quasi-static, and the time constant of the processes occurring in the sample is less than 1 / f mod , hence, sample M1 has a temporal follow-up to the influence of the periodically varying pump laser power. Note that this condition is satisfied in the used kHz modulation range, while in the MHz range this condition is considered less true.

[0044] The following table lists the material parameters and names of the sample M1 used in the process discussed. Silicon will be used to introduce the process later, so the corresponding material parameters of Si are also listed here:

[0045] R0=0,317 is the reflectivity of sample M1 at the sampling laser wavelength,

[0046] n0=3.58 is the refractive index of sample M1 at the sampling laser wavelength,

[0047] α bba =945cm -1 is the light absorption coefficient of sample M1 at the excitation laser wavelength,

[0048] β=–1,2×10 -22 cm -3 is the electro-optic coefficient at the sampling laser wavelength,

[0049] δ T =2,9×10 -4 K -1 is the thermo-optic coefficient at the sampling laser wavelength,

[0050] m e *=0,286m e is the effective mass of the electron,

[0051] m h *=0,36m e is the effective mass of the hole,

[0052] m e =9,1×10 -31 kg is the mass of an electron,

[0053] D a =10cm 2 s -1 is the ambipolar diffusion coefficient of excess charge carriers,

[0054] D t =κ / ρC=0,91cm 2 s -1 is the thermal diffusion coefficient of sample M1,

[0055] κ=1,5Wcm -1 K -1 is the thermal conductivity of sample M1 (at a temperature of 300 K),

[0056] ρ=2,32g cm -3 is the material density of sample M1,

[0057] C=0,71Jg -1 K -1 is the specific heat of sample M1 (at a temperature of 300 K),

[0058] A n =2,8×10 -31 cm 6 s -1 is the electron's Auger recombination coefficient,

[0059] A p =9,9×10 -32 cm 6 s -1 is the Auger recombination coefficient of holes,

[0060] U Aug (cm -3 s -1 )=A n (PN 2 -NN ie 2 )+A p (NP 2 -PN ie 2 ) is the Auger complex value,

[0061] U SRH (cm -3 s -1 )=(PN-N ie 2 ) / (τ P (N+N ie )+τ N (P+N ie )) is the Shockley-Read-Hall (SRH) composite value,

[0062] τ N =τ 0 N / (1+(N a +N d ) / P SRH ),

[0063] τ P =τ 0 P / (1+(N a +N d ) / N SRH ),

[0064] τ 0 N =2×10 -3 s is the SRH material parameter,

[0065] τ 0 P =2×10 -4 s is the SRH material parameter,

[0066] N SRH =P SRH =5×10 16 cm -3 is the SRH material parameter,

[0067] N ie =10 10 cm -3 is the intrinsic charge carrier concentration in sample M1,

[0068] P0(cm -3 )=[(N a -N d )+((N a -N d ) 2 +4N ie 2 ) 1 / 2 ] / 2 is the equilibrium hole concentration in sample M1,

[0069] N a (cm -3 ) is the acceptor dopant concentration in sample M1,

[0070] N d (cm -3 ) is the donor dopant concentration in sample M1,

[0071] N0(cm -3 )=N ie 2 / P0 is the equilibrium electron concentration in sample M1,

[0072] ΔN(cm -3 ) is the excess electron concentration,

[0073] ΔP(cm -3 ) is the excess hole concentration,

[0074] N=N0+ΔN is the total electron concentration,

[0075] P = P0 + ΔP is the total hole concentration,

[0076] σ def (cm 2 ) is the electron capture cross section of the main defect type in sample M1,

[0077] N def (cm -3 ) is the density of the main defect type in sample M1,

[0078] v th =(3k B T / m e *) 1 / 2 =2,09×10 7 cms -1is the hot electron velocity in sample M1 (at a temperature of 300 K), plane xy is the plane of the sample surface,

[0079] The direction z is the direction of the normal to the surface of the sample M1 (depth in the sample M1), ie the direction of the laser beam.

[0080] The PMR technical parameters required to apply the process in question, as well as the current values ​​for the examples given later, are as follows:

[0081] I pump (Wcm -2 ) is the power density of the excitation laser,

[0082] R las = 1,5 μm is the radius of the excitation and sampling laser spot,

[0083] f mod =2kHz is the excitation laser modulation frequency,

[0084] λ pump =808nm is the excitation laser wavelength,

[0085] λ probe =980nm is the sampling laser wavelength.

[0086] PMR signal analysis

[0087] The periodically varying pump laser power (AC excitation component) periodically generates excess charge carriers, electrons and holes, in the sample M1, with maximum concentrations of ΔN and ΔP. This results in periodic variations in the refractive index and reflectivity of the sample M1 (which decrease to ΔN) with maximum values ​​of |Δn| and |ΔR|. In addition, the sample temperature also varies periodically (increases to ΔN) with a maximum value of ΔT. The PMR signal, i.e. the relative change ΔR / R0 of the reflectivity of the sample M1, can be calculated as follows, see the already mentioned study by F. Dortu, T. Clarysse, R. Loo, B. Pawlak, R. Delhougne and W. Vandervorst "Progress in the physical modeling of carrier illumination":

[0088] ΔR / R0=[4 / (1-n0 2 )]{β(ΔN / m e *+ΔP / m h *)+δ T ΔT}+[4 / (1-n0 2 )]{β∫0∞cos(4πn0z / λ probe )[(dΔN / dz) / me *+(dΔP / dz) / m h *]dz+δ T ∫0∞cos(4πn0 z / λ probe )(dΔΤ / dz)dz} (1)

[0089] n0, R0, β and δ T is the sample M1 at the sampling laser wavelength λ probe The refractive index, reflection coefficient, electro-optic and thermo-optic coefficient at m e * and m h * are the effective masses of electrons and holes. For laser wavelengths typically used in single-crystal Si, these material parameters are known with high accuracy, e.g. probe =980nm, the parameters are: n = 3.58, R0 = 0.317, β = –1.2x10 -22 and β Τ =2.9x10 -4 K -1 (See the study by F. Dortu, T. Clarysse, R. Loo, B. Pawlak, R. Delhougne and W. Vandervorst: "Progress in the physical modeling of carrier illumination (Progress in physical modeling of carrier illumination, J. Vac. Sci. Technol., B 24, p. 1131, 2006)), m e * = 0.286 and m h *=0.36.

[0090] The second and third terms of equation (1) contain the gradients of the quantities ΔN, ΔP and ΔT in the z direction perpendicular to the plane of the sample M1 and sum the intensities of the components of the sampling laser beam reflected from the z depth due to the refractive index gradient, taking into account their phases. It will be shown below that in this case, the value of the terms including the integral is negligible compared to the first term.

[0091] With knowledge of ΔN, ΔP and ΔT, the value of the measured PMR signal can be calculated based on the first term on the right-hand side of equation (1), namely ΔR / R0. Due to the high power density of the excitation laser, ΔN=ΔP, where it is assumed that the generated excess charge carrier concentration is significantly higher than the basic doping level of the semiconductor sample. In the example given later, this condition is met.

[0092] (i) Assume that the defect concentration is constant with depth on the scale of the sampling laser wavelength.

[0093] (ii) Due to the initial depth-dependent distributions ΔN(z) and ΔP(z), the intensity of the excitation laser decreases with depth. pump (z)=I pump (0)exp(-α bba z), due to the total effective charge carrier lifetime τ tot Relatively short (because (D a τ tot ) 1 / 2 < <R p ), the vertical (z direction) charge diffusion can be ignored. Here, D a is the ambipolar diffusion coefficient of charge carriers, whose value is D a ~10cm 2 s -1 , where R p is the maximum penetration depth of ions.

[0094] (iii) Similarly, for the initial depth-dependent temperature distribution T(z), due to the effective lateral heat diffusion time constant τ tot Relatively short (because (D t τ t ) 1 / 2 < <R p , where D t ~1cm 2 s -1 is the lateral thermal diffusion coefficient), and the vertical (z direction) thermal diffusion can be ignored. Here, D t =κ / ρC, where κ=1,5W cm -1 K -1 , ρ=2,32g cm -3 , és C=0,71Jg -1 K -1 are the thermal conductivity, density and specific heat of Si single crystal.

[0095] Figure 2 The results show that the lightly doped (~10 -15 cm -3 ) Example of calculated ΔR / R0 values ​​for Si sample M1. Also indicated is the ΔR / R0 value of the defect-free reference Si sample M2. The ΔR / R0 value of the defect-free reference Si sample M2 is indicated by the thick horizontal line V1. The zero-value reflection change is marked by the dashed line V2. The calculation refers to the excitation laser wavelength λ pump =808nm, excitation laser power P las = 40 mW and a circular laser spot with a diameter of 3 μm. The electron capture cross section of the defect site is σ def =3×10 -15 cm 2. The calculations are based on equations (14) and (15), with the material parameters indicated in the conditions required to achieve the process. Even at a defect concentration of 1 ppb, there is a visible difference compared to the reference sample M2, so the reflectivity change is significant in the ppb-ppm range, and therefore the PMR method can be well used to determine the defect concentration and the lifetime assigned to it via measurements on a suitable reference sample M2. It should be noted that when the defect concentration is below about 0.1 ppm, the electro-optical effect prevails over the thermo-optical effect, in which case a significant excess charge carrier concentration can be maintained in sample M1, and the PMR signal shows negative values.

[0096] Figure 3a The results show that at different doses (10 11 -10 15 cm -2 ) with 1.5 MeV H + Simulation of the relationship between vacancy concentration and depth in the case of ion-implanted Si sample M1. The simulation was performed using the popular computer program SRIM (see SRIM: Stopping and Range of Ions in Matter, www.srim.org), with the Si material parameters generally fixed: the atomic displacement threshold energy is 15 eV, the density is 2.32 g cm- 3 The vacancy distribution was corrected with a defect survival probability of Cacc = 0.1 to take into account the presence of light H injected + Dense vacancy recombination processes occurring in a rare collision cascade caused by ions. It can be seen that the defect concentration hardly changes with depth and is therefore considered uniform in the evaluation method applied to PMR analysis. The vacancy concentration increases linearly with the implantation dose and varies in the range of about 1 ppb to 10 ppm. 10 14 cm -2 The implanted hydrogen concentration distribution of the dose is represented by line V3. The penetration depth of the ions is Rp~30, and the hydrogen concentration is R p nearby.

[0097] Figure 3b The results show that at different doses (10 11 -10 15 cm -2 ) with 1.5 MeV B + and As + SRIM simulation of the relationship between vacancy concentration and depth in the case of ion implanted Si sample M1. It can be seen that the penetration depth of ions is much smaller than that of hydrogen irradiation, and the vacancy concentrations of boron and arsenic irradiation are two and five orders of magnitude higher than those of hydrogen implantation of similar doses, as shown in line V4.

[0098] Figure 4The results show that at five different doses (10 11 -10 15 cm -2 ) with 1.5 MeV H + Ion implanted B lightly doped (about 10 15 cm -3 ) Measured PMR signal of p-type Si sample M1. Signal amplitude: PMR signal = 10 6 ×ΔR / R0. The measurement parameters are: excitation red laser wavelength λ pump =808nm, excitation red laser power P pump =40mW, modulation frequency f mod =2kHz, sampling infrared laser wavelength and power λ probe =980nm, P probe = 20 mW. The diameter of the laser spot is 3 μm. The zero reflection change is marked by the dashed line V5. The PMR signal is very sensitive within the ppb-ppm error concentration range estimated from the SRIM simulations, and it varies almost linearly on the logarithmic dose scale. 14 cm -2 The experimental value ΔR / R0 is different from the Figure 1 The values ​​calculated by the method shown are in good agreement, but the slope of the measured curve is almost constant and smaller than the calculated value. Figure 5 The possible reasons are explained.

[0099] Figure 5 The results show that at five different doses (10 11 -10 15 cm -2 ) with 1.5 MeV H + In the case of Si sample M1, ion implantation was performed using the method described according to Figure 4 The charge carrier lifetimes evaluated from PMR measurements are shown. The triangle 10 shows the values ​​for the non-implanted reference Si sample M2. The figure shows the total lifetime τ as a function of dose tot , the lifetime of Auger recombination τ Aug and the lifetime τ of the recombination at the defect site caused by the implantation determined in step S4 def . The horizontal dashed line τ a and τ t represents the characteristic time constant of bipolar charge carrier diffusion and thermal diffusion. It can be seen that at lower doses, the entire effective lifetime is dominated by bipolar diffusion, while Auger recombination plays a relatively small role in the entire dose range. As the dose and defect concentration increase, the recombination lifetime τ def gradually takes over the decisive role, because at the lowest dose, the lifetime τ def falls on the order of μs, while at medium doses it is close to the line τa Here, the total effective life is actually equal to the life value τ def The slope of the dotted line V6 is -1 / 2, so τ def It is inversely proportional to the square root of the dose, that is, the effective defect concentration (N def ) depends on the square root of the dose. This shows that N def has a sublinear dose dependence. One reason may be the recombination of Si vacancies and interstitials formed during dynamic thermal treatment and implantation, which may become more intense with increasing defect concentration. On the other hand, the diffusion of implanted hydrogen atoms promoted by implantation can also lead to the generation of hydrogen defect site complexes, as well as the passivation effect of hydrogen atoms bound to defect sites, which may lead to τ def The PMR measurements can therefore also provide information on in-situ defect recombination processes occurring during dynamic thermal treatments and implantation. Few measurement methods can provide similar quantitative information in the ppb-ppm error concentration range. Furthermore, the advantage of PMR is that it is a non-destructive and non-contact method. The evaluation of τ using the described method def and N def The reliability of this is also supported by the fact that for 1.5 MeV H + Implantation, others have also found a similar square root relationship between dose and effective defect concentration based on microwave photoconductivity transient (MW-PCD) measurements, for example, see the study by E. Gaubas et al. "Insitu analysis of the carrier lifetime in silicon during implantation of 1.5 MeV protons (In situ analysis of the carrier lifetime in silicon during implantation of 1.5 MeV protons, Lithuanian Journal of Physics, 50(4): 427-433, 2010)".

[0100] Electro-optic effect, generation of additional charge carriers

[0101] According to the following equation, the depth of sample M1 in the z direction can be determined at the optical frequency ν pump Working with power density I pump Excess charge carrier generation rate of the excitation (pump) laser (with a transverse (r) Gaussian intensity profile) illuminating sample M1:

[0102] G pump (z)=(I pump / hν pump )exp(-r 2 / Rlas 2 )(1-R0)α bba exp(-α bba z)(2)

[0103] Among them, R las is the characteristic radius of the laser spot, α bba is the absorption coefficient of the interband electronic transition of sample M1, for α bba =808nm, its value is α bba =945cm -1 . Know R las and α bba Afterwards, we can determine G pump An example of the value of can be found in the study of DEAspnes and AAStudna (Phys. Rev. B 27: 985-1009 (1983)).

[0104] The time derivative of the excess charge carrier concentration ΔN is:

[0105] dΔN / dt=G pump –ΔN(t) / τ tot (3)

[0106] Solving equation (3), we obtain:

[0107] ΔN(t)=G pump τ tot (1-exp(-t / τ tot ))(4)

[0108] Here, τ tot is the total effective characteristic lifetime of the excess charge carriers, including the effects of recombination and charge carrier diffusion, which means the characteristic time for charge carriers to disappear by recombination processes or lateral diffusion, i.e., in the xy plane starting from the area below the monitoring laser spot. It is obvious that in the case studied, τ tot Usually falls around 10 -8 -10 -9 s. Since τ tot <<1 / f mod , equation (4) can be further simplified:

[0109] ΔN(τ tot )=G pump τ tot (5)

[0110] According to this, ΔN follows G in time pump The modulation of τ can satisfy the quasi-static condition. tot It can be calculated using the following formula:

[0111] τ tot =(τ SRH -1 +τ Aug -1 +τ def -1 +τ a -1 ) -1 (6)

[0112] Among them, τ SRH , τ Aug and τ def is the lifetime of Shockley-Read-Hall (SRH), Auger and charge carrier recombination at the defect site, τ a is the characteristic time constant of the lateral bipolar charge carrier diffusion, representing the generation rate ΔG(x,y)~exp(-(x 2 +y 2 ) / R las 2 )=exp(-(r 2 ) / R las 2 The time lateral expansion of the charge packet ΔN(x,y) caused by τ has a two-dimensional Gaussian characteristic. Its value can be determined according to τ a =(eR las ) 2 / D a An estimate is made and can be assigned by evaluating the measured value of M2 of a reference sample (an unimplanted or clean sample that does not contain additional structural defects or unintentional impurities as recombination centers).

[0113] One of the keys to the method according to the invention is the expression of equation (6), where, as we know, in the previous discussion on the interpretation of PMR signals, in the calculation of τ tot The term τ introduced when def and τ a Not included in this form.

[0114] Returning to the integral of equation (1) involving the gradient dΔN / dz, based on equation (5), it can be seen that:

[0115] dΔN / dz=τ tot (dG pump / dz)=-τ tot α bba G0exp(-α bba z)(7)

[0116] Here, τ tot Usually about 10 -8 s(see Figure 4), G0 is the maximum value of the surface carrier generation rate of sample M1. By substituting equation (7) into the corresponding integral term of equation (1), the value ΔN~10 is obtained after integration. 15 cm -3 , which is similar to the first term of equation (1) (usually ΔN~10 18 cm -3 ) is negligible compared to , so the gradient term of the PMR signal can be omitted in the estimation.

[0117] The charge carrier lifetime τ belonging to a given recombination channel j and the composite coefficient U that can be assigned to the same channel j The relationship between them is:

[0118] ΔN / U j =τ j (8)

[0119] U j The values ​​of can be calculated using a well-known method for Auger and SRH processes and can be found in several places in the literature, where these terms have been detailed in the description of the conditions required for the operation of the procedure. It is worth noting that U Aug and U SRH Both depend on ΔN and ΔP. It should be emphasized that under the conditions during the PMR measurements (relatively high ΔN, ΔP values), SRH recombination is negligible compared to Auger recombination.

[0120] For the defect center to be inspected, ΔN / U def =τ def , where U def =σ def N def ΔNv th , where σ determined in steps S5 and S6 def and N def is the density of the composite cross section and defect center, v th is the thermal velocity of the charge carriers at room temperature. Therefore, knowing τ def ,L def =(σ def N def ) -1 Afterwards, the characteristic path length assigned to the defect complex can be determined and, knowing σ def Afterwards, N can also be obtained in step S7 def The value of σ defData on the value of can be found in the literature, for example, in the study of M.-L. David, E. Oliviero, C. Blanchard, JF Barbot for Si (Nucl. Instr. Meth. Phys. Res. B 186: 309–312, 2002). In the case of a divacancy, σ def =1-5×10 -15 cm 2 , for centers connected to vacancies, σ def =1-11×10 -15 cm 2 From the research of D. Macdonald and LJ Geerligs (Appl. Phys. Lett. 85 (18): 4061, 2004), it can be known that for interstitial metal impurities in Si, the electron capture cross section of Fe is σ def =5×10 -14 cm 2 , the electron capture cross section of Cr is σ def =2,3×10 -13 cm 2 , the electron capture cross section of V is σ def =5×10 -14 cm 2 σ of different defect centers in silicon def A useful summary of values ​​can be found in F. E. Lougieux, C. Sun, D. Macdonald (Solar Energy Materials and Solar Cells, 187: 263–272 (2018)).

[0121] Thermo-optical effect, increasing the temperature of sample M1

[0122] The excess free electrons generated by the excitation laser move from the valence band to the conduction band, and then, due to the energy of the excitation laser (hν pump =1.53eV) is larger than the band gap (E gap = 1.12 eV), the extra excess energy is transferred to the lattice via phonons, and their energy is reduced from the excited state to the energy level corresponding to the conduction band minimum. This relaxation occurs very quickly, taking about 10 -12 s, accompanied by rapid heat release (H hc , "hot electron" or "hot hole" heat source terms) and temperature rise. Due to the indirect band gap of Si, the excess charge carriers released from the conduction band minimum by electron-hole pair recombination are almost entirely released as heat (H recThe energy corresponding to the band gap is released in the form of a recombination heat source term ( , recombination heat source term). Recombination can occur via SRH and Auger processes or via defect sites. This further increases the temperature of the Si crystal. Higher temperatures increase the refractive index through the thermo-optic effect, which has the opposite effect to the electro-optic effect, which generally reduces the refractive index. The heat source term H hc and H rec And the temperature rise ΔT is calculated as follows:

[0123] H hc =G pump (h pump -E gap )(9)

[0124] H rec =(U Aug +U SRH +U def )E gap (10)

[0125] ΔT=(H hc +H rec )τ t / ρC(11)

[0126] Here, τ t is the characteristic time constant of lateral heat diffusion, which characterizes the temperature distribution with two-dimensional Gaussian characteristics ΔT(x,y)~exp(-(x 2 +y 2 ) / R las 2 The lateral diffusion over time. Its value can be based on τ t =(eR las ) 2 / D t is estimated and can be specified by evaluating the measured value of M2 from a reference measurement (i.e., an unimplanted or clean sample that does not contain additional structural defects or unintentional impurities that are treated as recombination centers). def The values ​​of all parameters except U can be considered known, and the value of ΔT can be used as def For the reference (undamaged or clean) sample M2, U def =0.

[0127] Return the integral of equation (1) involving the dΔT / dz gradient and consider:

[0128] Ud Aug / dz = (dU Aug / dΔN)(dΔN / dz) ≈ 3(A n + A p )ΔN2 (dΔN / dz) (12)

[0129] Ud def / dz = (dU def / dΔN)(dΔN / dz) = (σ def N def v th )(dΔN / dz) (13)

[0130] And using dΔN / dz and dG already described in equation (7) pump / dz form, the integral can be calculated. Its value is within the range of about 0,003-0,2℃ in ppb-ppm error concentration. This value is negligible compared to the value of the main term ΔT, which is similar to N def The values ​​usually fall within the range of about 1-10°C and determine the thermo-optical effect.

[0131] PMR signal evaluation procedure

[0132] Using the results of the above analysis, the PMR signal in the reference sample M2 without defect centers can be calculated with the following equation:

[0133] ΔR / R0| ref =|4 / (1-n0 2 )|{βΔN ref (1 / m e *+1 / m h *)+δ T (G pump (h pump -E gap )+(U SRH,ref +U Aug,ref )E gap )τ t / ρC}(14)

[0134] Here, U SRH,ref and U Aug,ref depends on the first and third powers of ΔN, and ΔR / R0 can be calculated for all values ​​of ΔN. Based on the experimentally determined ΔR / R0 | ref , the value of ΔNref can be determined in step S2 according to equation (14), and then U can be determined based on this result SRH,ref and U Aug,ref The value of .

[0135] The PMR signal in the sample M1 including the defect center injected in this example can be calculated using the following expression:

[0136] ΔR / R0| imp =|4 / (1-n02 )|{βΔN imp (1 / m e *+1 / m h *)+δ T (G pump (h pump -E gap )+(U SRH,imp +U Aug,imp +U def )E gap )τ t / ρC} (15)

[0137] For the damaged (implanted) sample M1, the experimentally determined ΔR / R0| from equation (15) is used in step S3. imp The value of ΔN is obtained imp For reference sample M2, ΔN ref =G pump τ ref , where τ ref is the total effective lifetime of the charge carriers. Meanwhile, in the damaged (injected) sample M1, ΔN imp =G pump τ imp , where τ imp is the total effective lifetime measured in the injected sample M1. pump The values ​​of appear in the undamaged and damaged samples M2, M1, therefore, they are based on the conditions listed in the description of the conditions required for the operation of the procedure, therefore, ΔN ref / τ ref =ΔN imp / τ imp , it can be seen that the composite factor that can be assigned to the defect implanted in sample M1 is as follows:

[0138] U def =(U Aug,ref –U Aug,imp )+(U SRH,ref –U SRH,imp )+(ΔN ref –ΔN imp ) / τ a (16)

[0139] Here, the U of reference sample M2 Aug,ref , U SRH,ref , ΔN ref The value of is already known from equation (14). Knowing ΔR / R0| imp After measuring the value of def Substituting into equation (15), we get ΔN of the tested sample M1: impvalue, then we know σ def N def and σ def , and get N def value, i.e., the desired defect concentration. It is worth noting that under the measurement conditions used, SRH recombination is usually negligible, which simplifies the form of equations (14), (15), and (16).

[0140] The method according to the invention can advantageously be used for MeV energy H + 、He +Implantation. In semiconductor technology, high energy ~MeV hydrogen ion implantation steps are commonly used. Due to their small mass, hydrogen ions penetrate deeper into a sample (such as silicon) than the larger donor (such as phosphorus, arsenic) or acceptor (such as boron) ions traditionally used. In addition, the defect concentration produced by hydrogen ion implantation is several orders of magnitude smaller than that of heavy ions implanted with similar doses and energies. High energy hydrogen implantation can control the conductivity of deep regions of the Si substrate, even tens of microns below the sample surface. By means of high-energy, low-dose hydrogen implantation, the lifetime of charge carriers can be modulated and the switching characteristics of various power electronic devices improved, an example of which can be found in the study by P. Hazdra, K. Brand, J. Rubes and J. Vobecky, “Local lifetime control by lightion irradiation: impact on blocking capability of power PiN diode (Microelectron. J. 32(5): 449-456, 2001)”, or in the study by A. Hallen, M. Bakowski and M. Lundqvist, “Multiple proton energy irradiation for improved GTO thyristors (Solid-State Electronics, 36 / 2: 133–141, 1993)”. When hydrogen is implanted in the medium dose range, donor centers can be formed, thereby forming buried n-type regions in complex semiconductor structures, see, for example, Y. Zohta, Y. Ohmura, and M. Kanazawa, "Shallow donor state produced by proton bombardment of silicon, J. Appl. Phys. 10(4): 532, 1971". High-energy hydrogen implantation is a common step in the design of electronic imaging devices (such as C-MOS cameras), which can be used in 10 11 -10 16 cm -2 Defects are formed at small ppb-ppm concentrations within the applied dose range, typically in the upper 10-100 microns of the sample in the thickness range.

[0141] The method according to the present invention can also be advantageously used for other high energy, low dose implantation and low dose channeling deep implantation. Here, the method can also be used to check the accuracy of sample orientation and accurately determine the cutting plane orientation of the sample, because the penetration depth of the implanted ions can be significantly increased, and the defect concentration caused by them can be greatly reduced by using channel implantation, for example, see M.Posselt, B.Schmidt, CS Murthy, T.Feudel and K.Suzuki's study "Modeling of damage accumulation during ion implantation intosingle-crystalline silicon (damage accumulation modeling of ion implantation process in single crystal silicon, J.Electrochem.Soc.144:1495, 1997)". In this case, the direction of the collimated ion beam with low divergence is parallel to any crystal axis of a semiconductor crystal with crystal orientation Si

[100] or Si

[110] , for example. The implanted ions then undergo a transverse oscillatory motion perpendicular to their direction of travel between parallel atomic rows and atomic planes of the crystal, as a result of which the probability of direct ion-atom collisions is reduced and the nuclear and electronic braking forces acting on the ions are also reduced. The channeling effect plays an important role below the low defect concentration range (typically 0.1-1%), above which the newly emerged defect centers already hinder this effect. On the other hand, the measurement of the channeling effect is also very sensitive to the precise setting of the sample orientation, which is also hindered by the typical inclination of the ion beam with respect to the main crystal axes of about 0.1-1°. The resulting defect concentration depends strongly on the dose and direction of the implantation. The proposed method is suitable for monitoring defect concentrations and charge carrier lifetimes, typically in the ppb-ppm defect concentration range, at a fixed dose with a variable tilt / twist angle or at a variable dose with a fixed tilt / twist angle. The procedure is also suitable for the precise determination of the cutting plane orientation of the substrate, i.e., the high-precision monitoring of the inclination angle of the sample surface to a given crystal direction, which differs from 90° by about 0.1°.

[0142] In high energy light injection (H + 、He + ) or even heavier injection (B + , P + 、As + ), in the case of channel implantation (dose-dependent channel blocking effect), procedures in the small defect concentration range can help monitor dose-dependent dynamic thermal processes during implantation, which can be considered an advantage. This enables more precise planning of implantation techniques used in the semiconductor industry.

[0143] The proposed method can be advantageously used to measure the concentration of homogeneous O, C contamination, oxygen crystal defect complexes or homogeneous metal contamination, and to estimate the associated lifetime.

[0144] Another advantage is that the method can also be applied to other semiconductor materials (e.g., silicon carbide (SiC), germanium (Ge), etc.) if the above-mentioned physical material parameters are known and the PMR method uses appropriate laser wavelength, laser power and modulation frequency.

Claims

1. A method for determining a crystal defect concentration of less than 10 ppm in a semiconductor material based on light modulated reflectometry, characterized in that: Injection (S1) of excess charge carriers into a sample of semiconductor material (M1) by means of a temporally periodically modulated irradiation, The optical reflectance modulation (ΔR) caused by the temporal variation of the excess charge carriers is defined by the amount of modulation produced in the reflection (R) of a test beam having a constant power over a period of time, by, forming a ratio (ΔR / R) of the optical reflectance modulation (ΔR) and the measured reflectance (R), The excess charge carrier concentration formed during the irradiation is deduced from the ratio obtained, The total charge carrier lifetime (τ tot ), From the total charge carrier lifetime (τ tot ) is derived from the recombination lifetime (τ def ), Based on this, the crystal defect concentration is determined (S7).

2. The method according to claim 1, characterized in that A semiconductor sample (M1) implanted with low-mass ions is measured by light-modulated reflectometry.

3. The method according to claim 1, characterized in that A semiconductor sample (M1) implanted with hydrogen or helium ions is measured by light modulation reflectometry.

4. The method according to claim 1, characterized in that: A semiconductor sample (M1) implanted with low-mass ions was measured by light-modulated reflectometry, wherein the implantation energy was chosen to be greater than 300 keV.

5. The method according to claim 1, characterized in that A semiconductor sample (M1) implanted with low-mass ions was measured by light-modulated reflectometry, where the implantation dose was chosen to be between 1e10 and 1e17 1 / cm 2 between.

6. The method according to any one of claims 1 to 5, characterized in that Most of the formed crystal defect concentration is located at a depth of 100 micrometers from the surface of the sample (M1).

7. The method according to any one of claims 1 to 6, characterized in that A semiconductor sample (M1) containing a crystal defect concentration caused by metal impurities in the semiconductor crystal is measured by light modulation reflectometry.

8. The method according to any one of claims 1 to 6, characterized in that A semiconductor sample (M1) including a crystal defect concentration caused by oxygen impurity complexes in the semiconductor crystal is measured by light modulation reflectometry.

9. The method according to any one of claims 1 to 8, characterized in that A semiconductor sample (M1) implanted with non-low-mass ions is measured by light-modulated reflectometry, where the following conditions are met: R las 2 <<R p 2 , Among them, R las is the laser spot radius for pumping and sampling PMR, R p is the maximum penetration depth of the implanted ions.

10. The method according to any one of claims 1 to 8, characterized in that A semiconductor sample (M1) implanted with non-low-mass ions and having a low defect concentration due to the channeling effect caused by the implantation conditions used is measured by light-modulated reflectometry.

11. The method according to any one of claims 1 to 8, characterized in that A semiconductor sample (M1) implanted with non-low-mass ions and having a low defect concentration caused by a channeling effect induced by the implantation conditions used is measured by light-modulated reflectometry, wherein the measured quotient ΔR / R shows a detectable dependence on the tilt angle between the ion beam direction and one of the main crystal axes of the sample (M1).

Citation Information

Patent Citations

  • Detecting thermal waves to evaluate thermal parameters

    US4579463A

  • Apparatus and method for evaluating a semiconductor wafer

    US6489801B1

  • Use of a coefficient of a power curve to evaluate a semiconductor wafer

    US6812717B2

  • Measuring characteristics of ultra-shallow junctions

    US8120776B1

  • Method for monitoring the performance of an ion implanter using reusable wafers

    WO1999008307A1